Investigating mobile motion prediction in supporting seamless handover for high speed mobile node - Yaakob, Naimah; Anwar, Farhat; Suryady, Zeldi; Hassan Abdalla Hashim, Aisha (Faculty of Engineering, International Islamic University Malaysia, 2008)
While witnessing the rapid development in the world of wireless communication, it is highly expected that the next generation of wireless network to be quickly adapt with the high Quality of Service (QoS) requirements and demands from mobile wireless users especially in real time and multimedia applications. Mobile IPv6 has been declared to be unsuitable for managing the mobility of end users running such stringent QoS specifications since the resulting latency and packet loss rate during handover are too high. To address the issue, various new and state-of-the-art protocols have been designed and developed, particularly to meet the demand for mobile Internet users. In this paper, we have investigated the effectiveness of mobile motion prediction technique in providing seamless handoff for high speed wireless environment where mobility prediction purpose is to obtain a priori information regarding the next Access Router (AR) the mobile node will move to. It was shown that the prediction information is found to be very helpful in establishing an advance connection with the new AR so that the high handoff latency and packet loss rate can be greatly reduced